Method for manufacturing a zinc anode, a zinc anode manufactured using the same, and a zinc ion battery containing the same

KR103018513B1Active Publication Date: 2026-09-15KOOKMIN UNIV IND ACAD COOP FOUND
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
KR1020240092075
Authority / Receiving Office
KR · KR
Patent Type
Patents
Current Assignee / Owner
Priority Date
2023-10-27
Filing Date
2024-07-12
Publication Date
2026-09-15
Estimated Expiration
2044-07-12

Smart Images

  • Figure 112024075614845-PAT00001_ABST
    Figure 112024075614845-PAT00001_ABST
Patent Text Reader

Abstract

The present invention discloses a method for manufacturing a zinc anode, a zinc anode manufactured using the same, and a zinc ion battery comprising the same. The present invention comprises the steps of: preparing a hexagonal boron nitride solution by mixing hexagonal boron nitride, a binder polymer, and a solvent; and preparing a zinc anode by spraying the hexagonal boron nitride solution onto a zinc foil; wherein the zinc anode comprises the hexagonal boron nitride scattered on the zinc foil.
Need to check novelty before this filing date? Find Prior Art

Description

Technology Field

[0001] The present invention relates to a method for manufacturing a zinc anode, a zinc anode manufactured using the same, and a zinc ion battery comprising the same. More specifically, the present invention relates to a method for manufacturing a zinc anode with improved stability through hexagonal boron nitride scattering, a zinc anode manufactured using the same, and a zinc ion battery comprising the same. Background Technology

[0003] A global consensus is forming regarding the severity of climate change caused by global warming. In line with this, the Korean government is introducing energy-related policies, such as the 2050 Carbon Neutrality and 2030 Renewable Energy Implementation Plans, and the related market size is growing rapidly. In particular, the importance of supplying clean energy is emerging as a means to replace fossil fuels, which are cited as the main culprit of global warming.

[0004] Representative methods for supplying clean energy include renewable energy generation, such as solar and wind power. However, renewable energy generation has the drawback of making continuous energy supply difficult, and to resolve this, the construction of large-scale energy storage systems is essential.

[0005] To store energy on a power plant scale, the development of eco-friendly, high-capacity, high-stability, low-cost, and low-risk batteries is essential. Accordingly, aqueous zinc-ion batteries are attracting attention as next-generation large-capacity energy storage devices. Zinc is inexpensive, has a low risk of depletion, and possesses a high theoretical capacity. Furthermore, since they can operate in aqueous environments, environmental hazards and the risk of explosion are significantly reduced.

[0006] The zinc foil used as the cathode reacts easily with the electrolyte to form an unstable interface, and during battery operation, zinc is deposited in a dendritic form on the surface of the zinc foil, which reduces active zinc and increases the risk of short circuits.

[0007] Therefore, the zinc foil used as the cathode reacts easily with the electrolyte to form an unstable interface, and there is a problem in that the separator is perforated by dendritic growth, causing a short circuit. Prior art literature

[0009] Korean Patent Publication No. 10-2024-0037807, "Electrolyte for aqueous zinc battery and aqueous zinc battery" Korean Patent Publication No. 10-2024-0071571, "Zinc electrode including an artificial protective layer for preventing dendrites, method for manufacturing the same, and zinc metal battery including the same" The problem to be solved

[0010] The embodiments of the present invention aim to provide a method for manufacturing a zinc anode capable of suppressing zinc dendrites and ensuring high stability by spraying hexagonal boron nitride (h-BN) onto a zinc foil at regular intervals using a spray process to produce a zinc anode, and assembling the zinc anode into an aqueous zinc ion battery, thereby providing a zinc anode manufactured using the same and a zinc ion battery containing the same.

[0011] The embodiment of the present invention aims to provide a method for manufacturing a zinc anode, a zinc anode manufactured using the same, and a zinc ion battery containing the same, wherein a zinc anode structure is designed in which bulk hexagonal boron nitride is obliquely positioned at regular intervals on a zinc foil to suppress zinc dendrites and thereby improve the stability of the battery. means of solving the problem

[0013] A method for manufacturing a zinc anode according to an embodiment of the present invention comprises the steps of: preparing a hexagonal boron nitride solution by mixing hexagonal boron nitride, a binder polymer, and a solvent; and preparing a zinc anode by spraying the hexagonal boron nitride solution onto a zinc foil, wherein the zinc anode comprises the hexagonal boron nitride scattered on the zinc foil.

[0014] The zinc anode above allows zinc to grow three-dimensionally by the hexagonal boron nitride.

[0015] The bonding angle of the hexagonal boron nitride with respect to the surface of the zinc foil may be 20° to 30°.

[0016] The above hexagonal boron nitride may be 10% to 20% by weight with respect to 100% by weight of the hexagonal boron nitride solution.

[0017] The binder polymer may be 1% to 2% by weight with respect to 100% by weight of the hexagonal boron nitride solution.

[0018] The binder polymer may include at least one of polyvinylidene fluoride (PVDF) and polytetrafluoroethylene (poly(1,1,2,2-tetrafluoroethylene); PTFE).

[0019] The above solvent may include at least one of N-methyl-2-pyrrolidone (hereinafter NMP), ethanol, and isopropyl alcohol.

[0020] The application time of the above ultrasound may be 30 to 60 minutes.

[0021] The spraying time of the above hexagonal boron nitride solution may be 4 to 12 seconds.

[0022] A zinc anode according to an embodiment of the present invention is manufactured according to a method for manufacturing a zinc anode according to an embodiment of the present invention and comprises a zinc foil; and hexagonal boron nitride scattered on the zinc foil.

[0023] The zinc anode above allows zinc to grow three-dimensionally by the hexagonal boron nitride.

[0024] The bonding angle of the hexagonal boron nitride with respect to the surface of the zinc foil may be 20° to 30°.

[0025] A zinc ion battery according to an embodiment of the present invention comprises: a zinc anode according to an embodiment of the present invention; a cathode positioned opposite to the zinc anode; a separator disposed between the zinc anode and the cathode; and an electrolyte filled between the zinc anode and the cathode; wherein the zinc anode comprises hexagonal boron nitride scattered on a zinc foil. Effects of the invention

[0027] According to an embodiment of the present invention, to suppress zinc dendrites, a zinc anode is manufactured by scattering hexagonal boron nitride (h-BN) at regular intervals on a zinc foil through a spray process to manufacture the zinc anode, and the zinc anode is assembled into an aqueous zinc ion battery to ensure suppression of dendrites and high stability therefrom, thereby providing a method for manufacturing a zinc anode, a zinc anode manufactured using the same, and a zinc ion battery including the same.

[0028] According to an embodiment of the present invention, to suppress zinc dendrites, a zinc anode structure is designed in which bulk hexagonal boron nitride is obliquely positioned at regular intervals on a zinc foil. An embodiment of the present invention, which can suppress zinc dendrites and improve the stability of the battery as a result, aims to provide a method for manufacturing a zinc anode, a zinc anode manufactured using the same, and a zinc ion battery including the same. Brief explanation of the drawing

[0030] FIG. 1 is a schematic diagram illustrating a method for manufacturing a zinc anode according to an embodiment of the present invention. FIG. 2 is a schematic diagram illustrating a comparison of the zinc growth process of a conventional zinc anode and a zinc anode according to an embodiment of the present invention, and FIG. 3 is a schematic diagram specifically illustrating the zinc growth process in a zinc anode according to an embodiment of the present invention. Figure 4 is a graph showing the X-ray diffraction analysis results of a zinc anode according to Example 1. Figure 5 is a graph showing the results of Raman spectroscopy analysis of a zinc anode according to Example 1. Figure 6 is a graph showing the results of X-ray photoelectron spectroscopy elemental identification of a zinc anode according to Example 1. FIG. 7 is an image showing the scanning electron microscope measurement results of the zinc anode according to Example 1 before the operation of the zinc ion battery according to Example 2-1, and FIG. 8 is an image showing the scanning electron microscope measurement results of the zinc anode according to Example 1 after the operation of the zinc ion battery according to Example 2-1. Figure 9 is an image showing the energy dispersive X-ray spectral analysis results of the zinc anode according to Example 1 before the operation of the zinc ion battery according to Example 2-1, and Figure 10 is an image showing the cross-sectional scanning electron microscope measurement results of the zinc anode according to Example 1 after the operation of the zinc ion battery according to Example 2-1. FIG. 11 is a graph showing the time-current method measurement results of a zinc ion battery according to Comparative Example 2 and a zinc ion battery according to Example 2-1, FIG. 12 is a graph showing the results of the rate characteristic evaluation, and FIG. 13 is a graph showing the results of the stability evaluation. FIG. 14 is an image showing the scanning electron microscope measurement results of the zinc anode according to Comparative Example 1 after the operation of the zinc ion battery according to Comparative Example 2, FIG. 15 is an image showing the scanning electron microscope measurement results of the zinc anode according to Example 1 after the operation of the zinc ion battery according to Example 2-1, and FIG. 16 is a digital photograph showing the zinc anode according to Comparative Example 1 and the zinc anode according to Example 1 after the operation of the battery. FIG. 17 is a graph showing the X-ray diffraction analysis results of the zinc anode according to Example 1 after the operation of the zinc ion battery according to Example 2-1, and FIG. 18 is a graph showing the ratio of the presence of (002) to (101) according to the X-ray diffraction analysis results of FIG. 17. FIG. 19 is a graph showing the cyclic amperage measurement results of a zinc ion battery according to Comparative Example 2 and a zinc ion battery according to Example 2-2, and FIG. 20 is a graph showing the electrochemical impedance spectroscopy measurement results. FIG. 21 is a graph showing the results of the rate characteristic evaluation of the zinc ion battery according to Comparative Example 2 and the zinc ion battery according to Example 2-2, and FIG. 22 is a graph showing the results of the stability evaluation. Specific details for implementing the invention

[0031] Embodiments of the present invention will be described in detail below with reference to the attached drawings and the contents described therein, but the present invention is not limited or restricted by the embodiments.

[0032] The terms used herein are for describing the embodiments and are not intended to limit the invention. In this specification, the singular form includes the plural form unless specifically stated otherwise in the text. As used herein, "comprises" and / or "comprising" do not exclude the presence or addition of one or more other components or steps mentioned in the description.

[0033] As used herein, terms such as “examples,” “examples,” “aspects,” “examples,” etc., are not to be interpreted as implying that any described aspect or design is superior or more advantageous than other aspects or designs.

[0034] Furthermore, the term 'or' refers to an inclusive or rather an exclusive or. That is, unless otherwise noted or is clear from the context, the expression 'x uses a or b' refers to any one of the natural inclusive permutations.

[0035] Additionally, singular expressions (“a” or “an”) used in this specification and claims should generally be interpreted to mean “one or more” unless otherwise stated or it is clear from the context that they relate to the singular form.

[0036] The terms used in the following description have been selected as common and universal in the relevant technical field, but other terms may exist depending on technological development and / or changes, conventions, preferences of the skilled technician, etc. Therefore, the terms used in the following description should not be understood as limiting the technical concept, but as illustrative terms to explain the embodiments.

[0037] In addition, in specific cases, there are terms arbitrarily selected by the applicant, and in such cases, their detailed meanings will be described in the relevant explanatory section. Therefore, the terms used in the description below must be understood not merely as their names, but based on their meanings and the content throughout the specification.

[0038] Unless otherwise defined, all terms used in this specification (including technical and scientific terms) may be used in a meaning that is commonly understood by those skilled in the art to which the present invention pertains. Additionally, terms defined in commonly used dictionaries are not to be interpreted ideally or excessively unless explicitly and specifically defined otherwise.

[0039] Meanwhile, in describing the present invention, if it is determined that a detailed description of related known functions or configurations could unnecessarily obscure the essence of the invention, such detailed description will be omitted. Furthermore, the terminology used in this specification is used to appropriately express embodiments of the present invention, and such terminology may vary depending on the intent of the user or operator, or the conventions of the field to which the invention belongs. Accordingly, the definitions of these terms should be based on the content throughout this specification.

[0041] FIG. 1 is a schematic diagram illustrating a method for manufacturing a zinc anode according to an embodiment of the present invention.

[0042] A method for manufacturing a zinc anode according to an embodiment of the present invention comprises the step (S110) of preparing a hexagonal boron nitride solution by mixing hexagonal boron nitride (e.g., bulk hexagonal boron nitride, 110), a binder polymer, and a solvent, and the step (S120) of manufacturing a zinc anode by spraying the hexagonal boron nitride solution onto a zinc foil (120), wherein the zinc anode comprises hexagonal boron nitride scattered on the zinc foil (120).

[0043] Accordingly, the method for manufacturing a zinc anode according to an embodiment of the present invention involves scattering hexagonal boron nitride (110) onto a zinc foil (120) through a spray process to produce a zinc anode in which hexagonal boron nitride (110) is positioned obliquely at regular intervals on the zinc foil (120). When this is applied to a zinc ion battery, the stability of the zinc ion battery can be improved by blocking the two-dimensional diffusion path of zinc ions during zinc deposition and suppressing the growth of zinc dendrites.

[0044] First, the method for manufacturing a zinc anode according to an embodiment of the present invention proceeds with the step (S110) of preparing a hexagonal boron nitride solution by mixing hexagonal boron nitride (e.g., bulk hexagonal boron nitride, 110), a binder polymer, and a solvent.

[0045] Hexagonal boron nitride (110) has a structure in which layers of nitrogen and boron bonded in a hexagon are stacked, and thus has very high electrical resistance and chemical stability. Accordingly, due to these characteristics, hexagonal boron nitride (110) has the advantage that even when voltage is applied to hexagonal boron nitride (110), charging phenomena and chemical reactions do not easily occur.

[0046] Hexagonal boron nitride (110) can have a bulk phase.

[0047] Hexagonal boron nitride (e.g., bulk hexagonal boron nitride, 110) may be 10% to 20% by weight with respect to 100% by weight of the hexagonal boron nitride solution. If the hexagonal boron nitride (e.g., bulk hexagonal boron nitride, 110) is less than 10% by weight, the viscosity of the solution is too low, so there is a problem of the hexagonal boron nitride clumping during the drying process. If it exceeds 20% by weight, the viscosity of the solution is too high, so there is a problem of the hexagonal boron nitride clumping during the coating process.

[0048] Binder polymers can act as adhesives by forming van der Waals bonds between hexagonal boron nitrogens.

[0049] The binder polymer may be 1% to 2% by weight with respect to 100% by weight of the hexagonal boron nitride solution. If the binder polymer is less than 1% by weight, there is a problem that the adhesive strength is insufficient, and if it exceeds 2% by weight, there is a problem that it hinders the diffusion of zinc ions.

[0050] The binder polymer may include at least one of polyvinylidene fluoride (PVDF) and polytetrafluoroethylene (poly(1,1,2,2-tetrafluoroethylene); PTFE).

[0051] The solvent may include at least one of N-methyl-2-pyrrolidone (hereinafter NMP), ethanol, and isopropyl alcohol.

[0052] Finally, the method for manufacturing a zinc anode according to an embodiment of the present invention proceeds with the step (S120) of manufacturing a zinc anode by spraying a hexagonal boron nitride solution onto a zinc foil (120).

[0053] Accordingly, the method for manufacturing a zinc anode according to an embodiment of the present invention can form commercially available bulk hexagonal boron nitride (110) on a zinc foil (120) in a quick and simple process using spray coating.

[0054] The thickness of the zinc foil (120) may be 25 micrometers to 100 micrometers, and if the thickness of the zinc foil (120) is less than 25 micrometers, there is a problem with holes forming, and if it exceeds 100 micrometers, there is a problem with coin cell assembly.

[0055] Hexagonal boron nitride (110) can be scattered onto zinc foil (120) through a compressed air spray process.

[0056] Hexagonal boron nitride (110) can be scattered randomly on zinc foil (120).

[0057] The compressed air spray process can spray hexagonal boron nitride (110) onto zinc foil (120) by putting a hexagonal boron nitride solution into a spray gun and changing the solution into fine particles with compressed air.

[0058] The spraying time of the hexagonal boron nitride solution may be 4 to 12 seconds. If the spraying time of the hexagonal boron nitride solution is less than 4 seconds, there is a problem that the scattered hexagonal boron nitride (110) does not effectively limit the two-dimensional diffusion of zinc ions, and if it exceeds 12 seconds, there is a problem that the hexagonal boron nitride (110) interferes with the three-dimensional diffusion of zinc ions.

[0059] The injection pressure of the hexagonal boron nitride solution can be 200 MPa to 400 MPa. If the injection pressure of the hexagonal boron nitride solution is less than 200 MPa, there is a problem that the solution does not spread evenly, and if it exceeds 400 MPa, there is a problem that too much solution is injected.

[0060] The step (S120) of manufacturing a zinc anode by spraying a hexagonal boron nitride solution onto a zinc foil (120) can be performed by evenly spraying and scattering the hexagonal boron nitride (110) onto the front surface of the zinc foil (120).

[0061] According to an embodiment, the method for manufacturing a zinc anode according to an embodiment of the present invention may further include the step (S120) of manufacturing a zinc anode by spraying a hexagonal boron nitride solution onto a zinc foil (120), and then the step (S130) of heat-treating the boron nitride solution sprayed onto the zinc foil (120).

[0062] The heat treatment step (S130) involves dispersing the hexagonal boron nitride solution (e.g., compressed air spray process) and then rapidly drying the hexagonal boron nitride solution at a heat treatment temperature, so that the hexagonal boron nitride (110) can be solidified by the binder polymer in the shape immediately after the spraying process (e.g., spray process).

[0063] For example, the heat treatment temperature can be 120 ℃.

[0064] A zinc anode according to an embodiment of the present invention can be manufactured using a method for manufacturing a zinc anode according to an embodiment of the present invention.

[0065] Therefore, the method for manufacturing a zinc anode according to an embodiment of the present invention can significantly improve the stability and discharge capacity retention of a zinc ion battery, and if this is applied to a large-capacity energy storage facility, it can lower the unit cost of an eco-friendly renewable energy generation facility and increase the proportion of renewable energy generation.

[0066] A zinc anode according to an embodiment of the present invention will be described in detail in FIGS. 2 and FIGS. 3 below.

[0068] FIG. 2 is a schematic diagram illustrating a comparison of the zinc growth process of a conventional zinc anode and a zinc anode according to an embodiment of the present invention, and FIG. 3 is a schematic diagram specifically illustrating the zinc growth process in a zinc anode according to an embodiment of the present invention.

[0069] A zinc anode (100) according to an embodiment of the present invention comprises a zinc foil (120) and hexagonal boron nitride (110) scattered on the zinc foil (120). At this time, the hexagonal boron nitride (110) may be fixed to the zinc foil (120) by a binder polymer (e.g., PVDF) so as to be bonded to have an inclination relative to the zinc foil (120) without falling off or lying down.

[0070] According to an embodiment of the present invention, the zinc anode (100) can grow zinc three-dimensionally by hexagonal boron nitride (110).

[0071] Hexagonal boron nitride (110) has a structure in which layers of nitrogen and boron bonded in a hexagon are stacked, and thus has very high electrical resistance and chemical stability. Accordingly, due to these characteristics, hexagonal boron nitride (110) has the advantage that even when voltage is applied to hexagonal boron nitride (110), charging phenomena and chemical reactions do not easily occur.

[0072] Therefore, when charging a zinc ion battery, even if the zinc anode is negatively charged, the hexagonal boron nitride (110) is electrochemically inert. Due to this property, the shape of the zinc electrically deposited on the zinc anode can be controlled.

[0073] During electro-deposition, the diffusion paths of zinc ions can be divided into two-dimensional and three-dimensional paths.

[0074] For example, if two-dimensional diffusion occurs as in a conventional zinc anode (10), it results in the basal surface of the zinc dendrite becoming larger, which can promote zinc dendrite growth.

[0075] Specifically, during the zinc deposition process, uncontrolled two-dimensional growth of zinc crystals may occur in the conventional zinc anode (10), and defective grain boundaries may occur, and in particular, protrusions are likely to form at the defects of the defective grain boundaries.

[0076] In addition, when electrical charging is generated for zinc deposition on a conventional zinc anode (10), a tip effect may occur on the protrusions on the surface of the conventional zinc anode (10). The tip effect means that a strong electric field is generated in a protruding area with a large curvature.

[0077] Therefore, in a conventional zinc anode (10), zinc is rapidly deposited on the protrusion where a strong electric field is generated, and a large dendritic structure can be formed.

[0078] On the other hand, in the zinc anode (100) according to an embodiment of the present invention, hexagonal boron nitride (110) scattered on the zinc foil (120) can act as electrochemically inert barriers. These barriers change the surface of the zinc foil (120) from a two-dimensional structure to a three-dimensional structure and obstruct the two-dimensional diffusion path of zinc ions, thereby reducing the basal plane of the dendritic structure and inhibiting dendritic growth.

[0079] Specifically, in the zinc anode (100) according to the embodiment of the present invention, the bulk hexagonal boron nitride (110) acts as an electrochemically stable barrier, thereby effectively suppressing the two-dimensional growth of zinc crystals and inducing three-dimensional growth. Through this, the zinc anode (100) according to the embodiment of the present invention minimizes the occurrence of defective grain boundaries that may develop into zinc dendrites in the future, and a stable zinc structure (a zinc structure in which corrosion resistance and reversible zinc deposition / desorption are possible, with (002) being dominant) is filled between the hexagonal boron nitride (110), thereby allowing a flat surface structure to develop.

[0080] Accordingly, in the zinc anode (100) according to an embodiment of the present invention, when the zinc is deposited during the zinc deposition process, the deposited zinc may include a high proportion of (002) crystal planes.

[0081] The higher the ratio of zinc (002) deposited on the zinc anode (100) according to the embodiment of the present invention, the more electrochemically stable the zinc structure can be deposited on the zinc anode (100) according to the embodiment of the present invention.

[0082] In addition, the zinc anode (100) according to an embodiment of the present invention may have hexagonal boron nitride (110) bonded diagonally on the zinc foil (120) at an angle.

[0083] Accordingly, the zinc anode (100) according to the embodiment of the present invention has hexagonal boron nitride (110) present diagonally rather than parallel to the zinc foil (120), thereby blocking the two-dimensional diffusion path of zinc ions and inducing the zinc to grow flat, which can inhibit the growth of the zinc resin.

[0084] The hexagonal boron nitride (110) may have a bonding angle (a) with respect to the surface of the zinc foil (120) of 20° to 30°.

[0085] A zinc anode (100) according to an embodiment of the present invention can be applied to an electrochemical device such as a zinc ion battery, a zinc metal battery, a zinc air battery, a zinc bromine battery, a zinc manganese dioxide battery, a nickel-zinc flow battery, a zinc secondary battery, or a zinc ion capacitor.

[0086] Preferably, the zinc anode (100) according to an embodiment of the present invention can be applied to a zinc ion battery, and a zinc ion battery including the zinc anode (100) according to an embodiment of the present invention will be described below.

[0088] A zinc ion battery according to an embodiment of the present invention comprises a zinc anode according to an embodiment of the present invention, a cathode positioned opposite to the zinc anode, a separator disposed between the zinc anode and the cathode, and an electrolyte filled between the zinc anode and the cathode, wherein the zinc anode comprises hexagonal boron nitride scattered on a zinc foil.

[0089] Accordingly, the zinc ion battery according to the embodiment of the present invention effectively suppresses the dendritic growth of the zinc anode, thereby delaying the time of short circuit occurrence compared to the conventional zinc anode (hereinafter Zn) and increasing the active zinc, so that the energy storage capacity can be improved.

[0090] A zinc ion battery according to an embodiment of the present invention may include a zinc anode according to an embodiment of the present invention as a zinc anode.

[0091] Zinc anodes can be deposited through a three-dimensional diffusion pathway of zinc ions via hexagonal boron nitride.

[0092] The bonding angle of hexagonal boron nitride to the surface of zinc foil can be 20° to 30°.

[0093] The cathode can be spaced apart to face the zinc anode.

[0094] The cathode is activated carbon, (α-MnO2, β-MnO2 2, γ-MnO 2, It may include at least one of δ-MnO2, MnO, Mn2O3, Mn3O4, V2O5, VO2, NaV3O8, LiV3O8, VS2 and polyaniline (PANI).

[0095] The separator is placed in the space between the zinc anode and the cathode and can serve to prevent a short circuit between the zinc anode and the cathode.

[0096] As long as the separator functions to physically separate the zinc anode and cathode, it may be used without special restrictions; in particular, it is desirable to use one that has low resistance to ion movement of the electrolyte and excellent electrolyte moisture retention capacity.

[0097] The separator may be made of a porous, non-conductive, or insulating material. Accordingly, the separator may be a porous polymer film, for example, a porous polymer film made of a polyolefin-based polymer comprising at least one of an ethylene homopolymer, a propylene homopolymer, an ethylene / butene copolymer, an ethylene / hexene copolymer, and an ethylene / methacrylate copolymer, used alone or by laminating them.

[0098] In addition, the separator may use a conventional porous nonwoven fabric, for example, a nonwoven fabric made of high-melting-point glass fibers, polyethylene terephthalate fibers, or cellulose, but is not limited thereto.

[0099] The electrolyte may include an aqueous electrolyte, and the aqueous electrolyte may include an aqueous solvent and a metal salt. In this case, the aqueous solvent may include water.

[0100] Additionally, the electrolyte may include a non-aqueous electrolyte, and the non-aqueous electrolyte may include a non-aqueous solvent and a metal salt. In this case, the non-aqueous solvent may include at least one of: a nitrile-based solvent such as acetonitrile, propionitrile, butyronitrile; a carbonate-based solvent such as dimethyl carbonate, diethyl carbonate, dipropyl carbonate, methyl ethyl carbonate, methylpropyl carbonate, ethyl propyl carbonate, ethylene carbonate, propylene carbonate, butylene carbonate; a ketone-based solvent such as acetone, cyclohexanone; an alcohol-based solvent such as methanol, ethanol, propanol, isopropanol; an amide-based solvent such as N,N-dimethylformamide, N,N-dimethylacetamide; a carbamate-based solvent such as 3-methyl-2-oxazolidone; and a sulfur-containing compound-based solvent such as sulfolane, dimethyl sulfoxide, or 1,3-propanesulfone.

[0101] The metal salt may include at least one of ZnSO4, Zn(NO3)2, Zn(CH3CO2)2, ZnCl2, ZnBr2, Zn[N(CF3SO2)2]2, Zn[N(C2F5SO2)2]2, Zn[N(C2F5SO2)(CF3SO2)]2, Zn(CF3SO3)2, Zn(C2F5SO3)2, and their hydrates.

[0102] The zinc ion battery according to the embodiment of the present invention can significantly improve the stability and capacity of the zinc ion battery in an inexpensive and practical manner, and if this is applied to large-capacity energy storage facilities, it can lower the cost of environmentally friendly renewable energy generation and increase the proportion of renewable energy generation.

[0104] Comparative Example 1: Zn

[0105] 0.025 mm (99.95%, Goodfellow) zinc was used.

[0107] Example 1: Zn SBN

[0108] 0.9 g of h-BN and 0.1 g of polyvinylidene fluoride (PVDF), which acts as an adhesive, are added to 5 mL of N-methyl-2-pyrrolidone (NMP), a solvent, and stirred for 1 hour.

[0109] A zinc anode (hereinafter Zn SBN) scattered with h-BN is prepared by spraying a stirred h-BN solution onto a zinc foil with compressed air for 8 seconds.

[0111] Comparative Example 2: Zn cell

[0112] A symmetric cell assembled in the order (Zn / glass fiber separator / Zn) was prepared using 2M ZnSO4 as the electrolyte.

[0114] Example 2-1: Symmetric cell

[0115] A symmetric cell assembled in the order of (Zn SBN / glass fiber separator / Zn SBN) was prepared using 2M ZnSO4 as the electrolyte.

[0117] Example 2-2: Full cell

[0118] A full cell assembled in the order of (α-MnO2 / glass fiber separator / Zn SBN) was fabricated using 2M ZnSO4 as the electrolyte.

[0120] Figure 4 is a graph showing the X-ray diffraction analysis results of a zinc anode according to Example 1.

[0121] Referring to Fig. 4, it can be crystallographically confirmed that zinc and h-BN are present in the zinc anode according to Example 1.

[0123] Figure 5 is a graph showing the results of Raman spectroscopy analysis of a zinc anode according to Example 1.

[0124] Referring to Figure 5, it can be seen that h-BN does not undergo chemical changes even after being scattered on zinc foil.

[0126] Figure 6 is a graph showing the results of X-ray photoelectron spectroscopy elemental identification of a zinc anode according to Example 1.

[0127] Referring to Fig. 6, it can be seen that zinc, boron, and nitrogen are present as a result of identifying the elements present in the zinc anode according to Example 1.

[0129] Figure 7 is an image showing the scanning electron microscope measurement results of the zinc anode according to Example 1 before the operation of the zinc ion battery according to Example 2-1, and Figure 8 is an image showing the scanning electron microscope measurement results of the zinc anode according to Example 1 after the operation of the zinc ion battery according to Example 2-1.

[0130] Referring to FIGS. 7 and FIGS. 8, it can be seen that zinc is deposited flatly on the zinc anode according to Example 1.

[0132] Figure 9 is an image showing the energy dispersive X-ray spectral analysis results of the zinc anode according to Example 1 before the operation of the zinc ion battery according to Example 2-1, and Figure 10 is an image showing the cross-sectional scanning electron microscope measurement results of the zinc anode according to Example 1 after the operation of the zinc ion battery according to Example 2-1.

[0133] Referring to FIGS. 9 and FIGS. 10, it can be seen that the zinc anode according to Example 1 has a flat zinc structure filled between h-BN.

[0135] FIG. 11 is a graph showing the time-current method measurement results of a zinc ion battery according to Comparative Example 2 and a zinc ion battery according to Example 2-1, FIG. 12 is a graph showing the results of the rate characteristic evaluation, and FIG. 13 is a graph showing the results of the stability evaluation.

[0136] Referring to FIG. 11, the current density of the zinc anode according to Comparative Example 1 continuously increases with deposition time, whereas the current density of the zinc anode according to Example 1 initially increases, and then from around 260 seconds, it becomes 8 mA cm⁻¹ -2 It can be seen that the current density converges.

[0137] This means that continuous two-dimensional zinc deposition occurs on the zinc anode according to Comparative Example 1, and that two-dimensional zinc deposition occurs only at the beginning of deposition on the zinc anode according to Example 1.

[0138] Therefore, it can be seen that the zinc anode according to Example 1 inhibits the two-dimensional growth of zinc by bulk phase h-BN and induces three-dimensional growth.

[0139] Referring to Fig. 12, the constant current rate characteristic evaluation result is 0.5 ~ 3 mA cm⁻¹ -2 It can be seen that at the current density, the zinc anode according to Example 1 exhibits a lower zinc deposition / desorption overpotential compared to the zinc anode according to Comparative Example 1.

[0140] Referring to Fig. 13, 3 mA cm -2 As a result of the constant current stability evaluation, it can be seen that the zinc anode according to Example 1 exhibits a lower zinc deposition / desorption overvoltage compared to the zinc anode according to Comparative Example 1 and maintains a stable cycle for approximately 10 times longer (500 hours).

[0142] FIG. 14 is an image showing the scanning electron microscope measurement results of the zinc anode according to Comparative Example 1 after the operation of the zinc ion battery according to Comparative Example 2, FIG. 15 is an image showing the scanning electron microscope measurement results of the zinc anode according to Example 1 after the operation of the zinc ion battery according to Example 2-1, and FIG. 16 is a digital photograph showing the zinc anode according to Comparative Example 1 and the zinc anode according to Example 1 after the operation of the battery.

[0143] Referring to FIGS. 14 to 16, it can be seen that a flatter and more uniform zinc structure is deposited on the zinc anode according to Example 1.

[0145] FIG. 17 is a graph showing the X-ray diffraction analysis results of the zinc anode according to Example 1 after the operation of the zinc ion battery according to Example 2-1, and FIG. 18 is a graph showing the ratio of the presence of (002) to (101) according to the X-ray diffraction analysis results of FIG. 17.

[0146] Referring to FIGS. 17 and 18, it can be seen that the zinc anode according to Example 1 has more (002) in the deposited zinc compared to the zinc anode according to Comparative Example 1.

[0147] (002) has excellent corrosion resistance, so it has low reactivity with the electrolyte, and more reversible zinc deposition / desorption can occur compared to other aspects.

[0149] FIG. 19 is a graph showing the cyclic amperage measurement results of a zinc ion battery according to Comparative Example 2 and a zinc ion battery according to Example 2-2, and FIG. 20 is a graph showing the electrochemical impedance spectroscopy measurement results.

[0150] Referring to FIG. 19, it can be seen that the zinc ion battery according to Example 2-2 has a higher capacitance and a lower oxidation / reduction overvoltage than the zinc ion battery according to Comparative Example 2.

[0151] Referring to FIG. 20, the zinc ion cell according to Example 2-2 was found to have a sharper and smaller semicircle in the Nyquist plot and a steeper slope in the straight section compared to the zinc ion cell according to Comparative Example 2. This means that the electrochemical reaction of the full cell assembled with the zinc anode according to Example 1 is faster, and it has lower charge transfer resistance and higher ion diffusion coefficient characteristics.

[0153] FIG. 21 is a graph showing the results of the rate characteristic evaluation of the zinc ion battery according to Comparative Example 2 and the zinc ion battery according to Example 2-2, and FIG. 22 is a graph showing the results of the stability evaluation.

[0154] Figures 21 and 22 show the electrochemical characteristics of a zinc ion battery according to Example 2-2, measured using a constant current charging / discharging method.

[0155] Referring to FIGS. 21 and 22, it can be seen that the zinc ion battery according to Example 2-2, which is a full cell assembled with a zinc anode according to Example 1, is superior to the zinc anode according to Comparative Example 1 in terms of capacity and discharge capacity retention in the evaluation of rate characteristics and stability.

[0157] As described above, although the present invention has been explained by limited embodiments and drawings, the present invention is not limited to the above embodiments, and various modifications and variations are possible from this description by those skilled in the art to which the present invention belongs. Therefore, the scope of the present invention should not be limited to the described embodiments, but should be defined by the claims set forth below as well as equivalents thereof. Explanation of the symbols

[0159] 10, 100: Zinc anode 110: Hexagonal boron nitride 30, 130: Zinc foil a: Bonding angle

Claims

Claim 1 A method for manufacturing a zinc anode comprising: a step of preparing a hexagonal boron nitride solution by mixing bulk hexagonal boron nitride, a binder polymer, and a solvent; and a step of preparing a zinc anode by spraying the hexagonal boron nitride solution onto a zinc foil; wherein the zinc anode comprises the hexagonal boron nitride scattered on the zinc foil, and the hexagonal boron nitride acts as an electrochemically inert barrier to obstruct the two-dimensional diffusion pathway of zinc ions, thereby causing the zinc to grow three-dimensionally. Claim 2 delete Claim 3 A method for manufacturing a zinc anode according to claim 1, characterized in that the bonding angle of the hexagonal boron nitride with respect to the surface of the zinc foil is 20° to 30°. Claim 4 A method for manufacturing a zinc anode according to claim 1, characterized in that the hexagonal boron nitride is 10% to 20% by weight with respect to 100% by weight of the hexagonal boron nitride solution. Claim 5 A method for manufacturing a zinc anode according to claim 1, characterized in that the binder polymer is 1% to 2% by weight with respect to 100% by weight of the hexagonal boron nitride solution. Claim 6 A method for manufacturing a zinc anode according to claim 1, wherein the binder polymer comprises at least one of polyvinylidene fluoride (PVDF) and polytetrafluoroethylene (poly(1,1,2,2-tetrafluoroethylene); PTFE). Claim 7 A method for preparing a zinc anode according to claim 1, wherein the solvent comprises at least one of N-methyl-2-pyrrolidone (hereinafter NMP), ethanol, and isopropyl alcohol. Claim 8 A method for manufacturing a zinc anode according to claim 1, characterized in that the spraying time of the hexagonal boron nitride solution is 4 seconds to 12 seconds. Claim 9 A zinc anode manufactured according to the method for manufacturing a zinc anode according to claim 1, comprising: a zinc foil; and bulk-form hexagonal boron nitride scattered on the zinc foil; wherein the hexagonal boron nitride acts as an electrochemically inert barrier to obstruct the two-dimensional diffusion path of zinc ions, thereby causing the zinc to grow three-dimensionally. Claim 10 delete Claim 11 A zinc anode according to claim 9, characterized in that the bonding angle of the hexagonal boron nitride with respect to the surface of the zinc foil is 20° to 30°. Claim 12 A zinc ion battery comprising: a zinc anode according to claim 9; a cathode positioned opposite to the zinc anode; a separator disposed between the zinc anode and the cathode; and an electrolyte filled between the zinc anode and the cathode; wherein the zinc anode comprises bulk-form hexagonal boron nitride scattered on a zinc foil, and the hexagonal boron nitride acts as an electrochemically inert barrier to obstruct the two-dimensional diffusion path of zinc ions, thereby causing the zinc to grow three-dimensionally.

Citation Information

Patent Citations

  • Aqueous and hybrid electrolytes with wide electrochemical stability windows

    KR1020180105631A

  • High-capacity battery electrodes with improved binders, structures, and performance

    KR1020190086548A

  • anode protective layer

    KR1020220034815A

  • Shape-adaptable cable-type flexible alkaline metal battery

    KR102565802B1